(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Number of techniques are available to purify water, it include reduction, precipitation, ion exchange, electrochemical reduction and reverse osmosis. Most of them involve high capital costs with recurring expenses, which are not suitable for small-scale industries. Bio-technique has attracted the attention due to its effectiveness and environmentally benign nature. In bio techniques, agro wastes may be the potential sources for producing bio-adsorbents, which can be used for improving the quality of west water. Banana peel and Orange peel are also used as adsorbents for purification of water. Using natural resources upto it’s extend and making water palatable and is the need of the hour specially in developing and underdeveloped counties. Present work emphasizes use of banana peel as bio adsorbent in water purification unit. The designed water purification unit shows remarkable result in limits of purification of water.